Sales System at a Web-Based Cika Ciki Snack Shop - Lia Iftitah; Arif Senja Fitrani (Procedia of Engineering and Life Science, 2022)
Cika Ciki Snack Shop is one of the agents that sells a variety of snacks from various brands, but the store owner has problems promoting the products he sells, the longer it takes, the more competitors there are other snack agents, then Cika Ciki Snack Shop utilizes technology to market products. Therefore, the author created a website-based sales information system to develop a business in terms of sales. to make it easier for store owners to promote snacks and make it easier for customers to make purchases. This research was made using a Website-based information system with the waterfall method, and MySQL as the database, which is the data collection of anything snack along with the brand name provided by Cika Ciki Snack Store.